Impact of allogeneic blood transfusions on clinical outcomes in severely burned patients. Issue 5 (August 2020) - Kaserer, Alexander; Rössler, Julian; Slankamenac, Ksenija; Arvanitakis, Michael; Spahn, Donat R.; Giovanoli, Pietro; Steiger, Peter; Plock, Jan A.
Highlights: Blood transfusions are common in the treatment of severely burned patients. Transfusions are associated with a number of adverse events. Associated adverse events are higher infection rates and thromboembolic morbidity. Transfusions are also associated with a longer hospital stay. Abstract: Background: Allogeneic blood transfusions are common in the treatment of severely burned patients as surgery may lead to major blood loss. However, transfusions are associated with a number of adverse events. Therefore, the purpose of our study was to investigate the impact of allogeneic blood transfusions on clinical outcomes in severely burned patients. Methods: This retrospective study included all adult patients admitted to the burn center of the University Hospital Zurich between January 2004 and December 2014, with burn injuries greater than 10% of total body surface area and receiving both surgical and intensive care treatment. Primary Endpoints were infectious or thromboembolic complications and mortality and secondary endpoints were length of hospital and ICU stay. Simple and multivariable logistic and linear regression models, adjusted for injury severity and confounders, were applied. Results: 413 patients met inclusion criteria of which 212 patients (51%) received allogenic blood products. After adjustment for injury severity and confounders, red blood cell transfusion was independently associated with wound infection (OR 13.5, 95% CI 1.7–107, p = 0.014), sepsis (OR 8.3, 4.2–16.3; p < 0.001), pneumonia (OR 4.7, 2.2–10.0; p < 0.001), thrombosis (OR 3.0, 1.2–7.4; p = 0.015), central line infection (OR 34.7, 4.6–260; p = 0.001) and a longer ICU and hospital stay (difference 17.7, CI 12.1–23.4, p < 0.001 and 22.0, 15.8–28.2, p < 0.001, respectively). Fresh frozen plasma transfusion was independently associated with a longer ICU and hospital stay (difference 13.7, 95% CI 5.5–21.8, p = 0.001 and 13.5, 4.6–22.5, p = 0.003, respectively). Platelet transfusion was independently associated with systemic inflammatory response syndrome (OR 4.5, 1.3–15.5; p = 0.018) and mortality (OR 5.8, 2.1–16.0; p = 0.001). Conclusion: Transfusion of allogeneic blood products is associated with an increased infection rate and thromboembolic morbidity and a longer hospital stay in severely burned patients.